Polyvascular disease, pulse pressure and mortality: the Ludwigshafen Risk and Cardiovascular Health (LURIC)study : original communication - Yazdani, Babak; Kleber, Marcus E.; Yücel, Gökhan; Delgado Gonzales de Kleber, Graciela; Husain-Syed, Faeq; Krüger, Bernd; März, Winfried; Schwenke, Kay; Sigl, Martin; Krämer, Bernhard (Vasa, 2022)
Summary:Background: Peripheral arterial disease (PAD), coronary artery disease (CAD) and carotid stenosis (CS) are robust predictors of mortality. The value of individual vascular beds in polyvascular disease (PVD) to predict mortality in patients with atherosclerotic burden is not clear. Therefore, we have examined the predictive value of PAD, CAD and CS in patients at intermediate to high risk of cardiovascular (CV) disease. Patients and methods: In our retrospective observational study we analyzed baseline data from the Ludwigshafen Risk and Cardiovascular Health (LURIC) study, a monocentric cohort study of 3316 patients referred to coronary angiography. Results: As the number of atherosclerotic vascular beds increased, the hazard ratios (HRs) for both all-cause mortality and CV mortality significantly increased in a multivariate analysis after adjusting for age, sex, body mass index, diabetes mellitus and estimated glomerular filtration rate, with HRs of 1.36 (95%CI: 1.11-1.68), 2.56 (95%CI: 2.01-3.26), 2.84 (95%CI: 1.93-4.17) and 1.56 (95%CI: 1.19-2.06), 2.70 (95%CI: 1.97-3.72), 3.50 (95%CI: 2.19-5.62), respectively. The combination of PAD with either CAD or CS was associated with higher HRs for all-cause (HR 2.81 and 7.53, respectively) and CV (HRs 2.80 and 6.03, respectively) mortality compared with the combination of CAD and CS (HRs 1.94 and 2.43, respectively). The presence of PVD was associated with higher age, systolic blood pressure, pulse pressure (PP; a marker of vascular stiffness), former smoking and inversely with lower eGFR. Conclusions: We show that as the number of atherosclerotic vascular beds increases, all-cause and CV mortality rates increase in parallel. Simultaneous prevalence of PAD is associated with significantly higher all-cause and CV mortality rates compared with CS coexistence. Furthermore, increasing atherosclerotic load may contribute to vascular stiffness and impaired renal function.